The Births of New Private-Owned Enterprises in an Environment of State-Owned Enterprises - Zhong Zhao; Liang Zheng (Institute of Labor Economics (IZA), 2023)
The impact of the incumbent state-owned enterprises (SOEs) on the births of new private-owned enterprises (POEs) in China is a central concern for the government and society. In this paper, we apply agglomeration theories to distinguish the linkages between SOEs and POEs. Using China's 2008 economic census, the 2007 Input-Output Table, and the 2005 population mini census, we measure the formation of new POEs at the city-industry level, and the agglomeration forces of distance proximity to inputs, outputs, labor, and technology. More explicitly, we measure the extent to which local SOEs provide relevant inputs, consume outputs, employ similar workers, and use similar technology. Our findings indicate that overall, incumbent SOEs hinder the formation of new POEs. For manufacturing, the entry of new POEs is significantly lower in places where more upstream SOEs are concentrated. For services, the entry of new POEs is significantly lower in places where more upstream and downstream SOEs are concentrated. However, the agglomeration effects from the incumbent POEs are either insignificant or significantly positive.
Keywords: L26; L60; L80; R10; R12; 330; new firm formation; state-owned enterprise; firm ownership; agglomeration